Un dispositif de formation de formateurs en éducation au développement durable : analyse critique et perspectives - Didier Mulnet (Éducation et Socialisation, 2013)
The analysis of the pluricatégoriel training (University Diploma training trainers in education for sustainable development) asks the question of the terms and issues of training in education for sustainable development. This training aims to train managers able to manage training plans ESD, studies and investigations in relation to sustainable development, team teaching and training systems face or in Open Distance Education. The frameworks of sustainable development, of his education and training of trainers, having served as a basis for the development of this curriculum. The training will then be described. A critical analysis of the curriculum at the technical, conceptual and pedagogical will be offered from bibliographic data and feedback. Prospects for future training will be discussed by considering the evolution of business in different contexts, the link between training and trainer training engineering between research and the field, between the sciences and the humanities. Issues in terms of values and employment will also be analyzed critically.